Multipacting simulation in input power couplers of electron linear accelerator - Gusarova, M.A.; Zvyagintsev, V.L.; Petrushina, I.I. (Вопросы атомной науки и техники, 2013)
This paper concerns the results of multipacting prediction for the feeding waveguide section of the eLINAC accelerator. The threshold values of the input power, at which the discharge may occur in this structure, were obtained. Simulations were carried out analytically and numerically with various codes. The results of simulation were compared to each other. Рассмотрены вопросы возможности возникновения мультипакторного разряда в устройстве ввода мощности eLINAC. Определены пороговые уровни передаваемой мощности, при которой возможно развитие мультипакторного разряда, и выявлены наиболее подверженные разряду области. Розглянуто питання можливості виникнення мультипакторного розряду в пристрої введення потужності eLINAC. Визначено порогові рівні переданої потужності, при якій можливий розвиток мультипакторного розряду, та виявлено найбільш схильні області до розряду.